Strengthening Business Process Modeling with the Application / Combination of Viable System Model in ICT Policy Analysis Context (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Information and Communication Technology (ICT) policy is a code that clarifies the duties, responsibilities and rights of technology stakeholders and specifies acceptable and efficient ICT utilization. ICT policy life cycle encompasses four main processes which are: development, implementation, monitoring and evaluation. In many cases, the processes that form the life cycle of ICT policy usually stopped or failed at starting phase(s), including th e case study in this research (one of the Malaysian Public Institutions of Higher Education). Failures in ICT policy management may compromise ICT security, control and strategy in addition to incurring unnecessary expense. This paper discusses the methods utilized in conducting the study. Qualitative research and case study method were utilized to provide greater insight into this complicated phenomenon. An in-depth analysis and elaboration was performed using Viable System Model (VSM) and Hermeneutics method to diagnose and identify weaknesses, mismatches and viable requirements. The proposed model combined the perspectives of systemic functions and organizational structure of VSM with organizational processes and entities of Business Process Modeling (BPM). The application of VSM accommodated environmental dynamism, encouraged sustainable development and provided a sound theoretical platform. In combination with BPM, emphasis shifted from a specific, isolated policy domain to a business process model designed to manage overall ICT policy. An ICT policy management prototype was also developed based on the model. The model and prototype system have been verified through the case study.